Scientific Schools Created in Uzbek Linguistics - Ulug‘bek qizi , Usmonova Mohinur (Miasto Przyszłości, 2025)
The article discusses the concept of scientific schools, the scientific schools established in Uzbek linguistics, and their directions. The activities of the founders of these schools and their contributions are elaborated, detailing the tasks and achievements of scientific schools. Additionally, thoughts are presented on the formation and branches of the Uzbek Practical Linguistics scientific school, which emerged as a social need of the century.